2012
DOI: 10.1007/s10815-012-9804-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of in vitro fertilization in patients with proven poor ovarian responsiveness after early vs. mid-follicular LH exposure: a prospective, randomized, controlled study

Abstract: Adding LH to FSH from day 1 or from day 7 of ovarian stimulation in a GnRH-agonist long protocol exerts comparable effects on IVF outcome in poor responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
2
6
2
Order By: Relevance
“…An interesting finding was reported by Revelli et al ( 9 ). A total number of 848 IVF patients with the same base line characteristics were recruited in a real life population study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…An interesting finding was reported by Revelli et al ( 9 ). A total number of 848 IVF patients with the same base line characteristics were recruited in a real life population study.…”
Section: Discussionsupporting
confidence: 64%
“…LH activity can be administered in different forms, either adding r-LH to recombinant follicle stimulating hormone (rFSH) or using highly purified human menopausal gonadotropine (hMG) which provides follicle stimulating hormone and exogenous LH activity ( 1 , 2 , 4 , 5 ). Although Hill and Alvigi showed superiority of adding exogenous LH to rFSH over FSH alone in terms of increased number of mature oocytes, good quality zygotes and higher implantation rates but other investigators reported no improvement in the outcomes when exogenous LH is added ( 6 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, other cleavage rate comparison between groups were statistically similar. studies which reporting a higher embryo ploidy rate and a lightly higher pregnancy rate [12], although in our study we only found the correlation with chemical pregnancy.…”
Section: Discussioncontrasting
confidence: 87%
“…The favorable effect of LH addition in combination with FSH for follicular stimulation during IVF in poor responders or older women has been supported by some studies. [1719] Alberto Revelli's group [4] also reported that the addition of LH at early and mid-follicular stage have comparable effects on the IVF outcome in poor responders. However, in normogonadotropic women, the effect of LH addition remains unsettled.…”
Section: Discussionmentioning
confidence: 99%
“…[13] LH induces theca cells of developing follicles to produce androgens and polypeptide growth factors which enhance follicular response to FSH during follicular recruitment and selection. [4,5] Besides, LH could also stimulate the growth of large antral follicles. [6,7]…”
Section: Introductionmentioning
confidence: 99%